A subunit vaccine based on P97R1, P46, P42, and P65 from Mycoplasma hyopneumoniae can induce significant immune response in piglets - He, Yintao; Xie, Kaiyuan; Yuan, Zhongmao; Ouyang, Ting; Dong, Anran; Ling, Bing; Zeng, Weijun; Fang, Yiqi; Song, Yiwan; Wang, Lianxiang; Ding, Hongxing; Zhao, Mingqiu; et al. (Frontiers in Veterinary Science, 2024)
Mycoplasma pneumonia (MPS), caused by Mycoplasma hyopneumoniae (Mhp), is a chronic, airborne respiratory disease that poses a significant threat to the global swine industry. The P97 and P46 proteins are major antigens of Mhp, with the R1 region of P97 possessing full adhesive capability. Studies have shown that the main antigenic regions of Mhp P42 and P65 proteins exhibit strong immunogenicity. In this study, we first linked the genes encoding P97R1 and P46 proteins to form the P97R1P65 gene and subsequently constructed three shuttle plasmids: pFBD-P97R1P46, pFBD-P97R1P46-p65, and pFBD-P65-P42. These proteins were expressed using the Bac to Bac system and formulated into subunit vaccines for mouse immunization. Mouse experiments indicated that the P97R1P46 + P65-P42 protein combination elicited higher levels of specific antibodies, IL-2, IL-4, and CD8+ T cells compared to other subunit vaccine groups, a finding further validated in subsequent mouse challenge protection experiments. Therefore, we utilized the MultiBac expression system to co-express P97R1P46, P65, and P42 proteins in the pFastMultibacDual vector for immunization experiments in piglets. The piglet immunization experiments demonstrated that the Mhp subunit vaccine prepared in this study could induce specific antibodies against Mhp, with the combination of P97R1P46, P65, and P42 proteins inducing the highest level of humoral immunity. This study provides valuable insights for the development of Mhp subunit vaccines.